Continuous, non-invasive measurement of the haemodynamic response to submaximal exercise in patients with diabetes mellitus: evidence of impaired cardiac reserve and peripheral vascular response. Issue 1 (22nd October 2009) - Joshi, D; Shiwalkar, A; Cross, M R; Sharma, S K; Vachhani, A; Dutt, C
Abstract : Background: Reduced exercise capacity in diabetics has been attributed to limitations in cardiac function and microvascular dysfunction leading to impaired oxygen supply and nutritive perfusion to exercising muscles. Objective: To study changes in cardiac function and microvascular utilisation during exercise in diabetic individuals compared to age-matched controls. Methods: Diabetics with glycosylated haemoglobin (HbA1c ) <8 (n = 31), diabetics with HbA1c ⩾8 (n = 38) and age-matched non-diabetic controls (n = 32) performed exercise at 50 W for 10 minutes followed by recovery, with continuous monitoring of cardiac function by impedance cardiography and regional flow and oxygen saturation by laser Doppler and white light spectroscopy. Results: In the diabetics, cardiac reserve during exercise and cardiac overshoot during recovery are significantly reduced because of reduction in capacity to increase stroke volume. Regional flow to the exercising muscle is reduced and there is also disproportionately greater desaturation of the regional flow. Abnormalities in cardiac function and regional perfusion are related to the severity of diabetes. Conclusion: Cardiac response to exercise is attenuated significantly in diabetic individuals. Simultaneously, there is impairment in the regional distribution. These changes could be the harbinger of reduced exercise capacity in diabetics.